MCTS 70-640 : Windows server 2008 active directory, configuring - Poulton, Don (Exam cram., 2009)
MCTS Exam Cram Windows Server 2008 Active Directory, Configuring Exam 70-640 Don Poulton Covers the critical information you'll need to know to score higher on Exam 70-640! Utilize new features of Windows Server 2008 related to Active Directory Install and configure Active Directory forests and domains Plan and implement an Organizational Unit structure Plan and manage Active Directory infrastructure components, such as operations masters, global catalogs, read-only domain controllers, and sites Plan, implement, and manage Active Directory using Group Policy Plan and manage Active Directory roles, including Active Directory Lightweight Directory Services, Active Directory Rights Management Services, and Active Directory Federation Services Deploy software in Active Directory using Group Policy Utilize Active Directory features to manage users and groups Back up and restore Active Directory, and rebuild an Active Directory domain controller from backup Deploy and manage a public key infrastructure using Active Directory Certificate Services CD Features MeasureUp Practice Questions! Detailed explanations of correct and incorrect answers Multiple test modes Random questions and order of answers Coverage of each 70-640 exam objective WRITTEN BY A LEADING EXPERT: Don Poulton, MCSA, MCSE, A+, Network+, Security+, has been involved in consulting with small training providers as a technical writer, during which time he wrote training and exam prep materials for Windows NT 4.0, Windows 2000, and Windows XP. More recently, he has written or co-authored several certification volumes on Security+, Windows XP, Windows Server 2003, and Windows Vista, published by Que Publishing. informit.com/examcram ISBN-13: 978-0-7897-3791-5 ISBN-10: 0-7897-3791-4.